Understanding Indian supply chain management practices. (1st January 2013) - Park, Daewoo; Chinta, Ravi; Assudani, Rashmi; Lee, Mina; Cunningham, Margaret
Global corporations increasingly pursue avenues for employing the information technology and manufacturing prowess of India and managing global cooperative strategies (strategic alliance and supply networks) with India partners. While most studies addressing global cooperative strategies analyse organisational and industrial characteristics, very few theories incorporate explanations for Indian supply chain management practices. This study is an attempt to better understand Indian supply chain management practices.